The stereochemistry of amide side chains containing carboxyl groups influences water exchange rates in EuDOTA-tetraamide complexes - Mani, Tomoyasu (2013)
Many Eu(III) complexes formed with DOTA-tetraamide ligands (where DOTA is 1,4,7,10-tetraazacyclododecane-1,4,7,10-tetraacetic acid) have sufficiently slow water exchange kinetics to meet the slow-to-intermediate condition required to serve as chemical exchange saturation transfer (CEST) contrast agents for MRI. This class of MRI contrast agents offers an attractive platform for creating biological sensors because water exchange is exquisitely sensitive to subtle ligand stereochemistry and electronic effects. Introduction of carboxyl groups or carboxyl ethyl ester groups on the amide substituents has been shown to slow water exchange in these complexes, but less is known about the orientation or position of these side-chain groups relative to the inner-sphere Eu(III)-bound water molecule. In this study, a series of Eu(III) complexes having one or more carboxyl groups or carboxyl esters at the δ-position of the pendant amide side chains were prepared. Initial attempts to prepare optically pure EuDOTA-[(S)-Asp](4) resulted in a chemically pure ligand consisting of a mixture of stereochemical isomers. This was traced to racemization of (S)-aspartate diethyl ester during the synthetic procedure. Nevertheless, NMR studies of the Eu(III) complexes of this mixture revealed that each isomer had a different water exchange rate, differing by a factor of 2 or more. A second controlled synthesis and CEST study of EuDOTA-[(S)-Asp](4) and cis-EuDOTA-[(S)-Asp](2)[(R)-Asp](2) confirmed that the water exchange rates in these diastereomeric complexes are controlled by the axial versus equatorial orientation of the carboxyl groups on the amide side chains. These observations provide new insights toward the development of even more slowly water exchanging systems which will be necessary for practical in vivo applications.